Exposure assessment of monoterpenes and styrene: a comparison of air sampling and biomonitoring. Issue 8 (25th July 2003) - Liljelind, I; Rappaport, S; Eriksson, K; Andersson, J; Bergdahl, I A; Sunesson, A-L; Järvholm, B
Abstract : Background: Within- and between-worker variance components have seldom been reported for both environmental and biological data collected from the same persons. Aims: To estimate these variance components and their ratio for air contaminants and urinary metabolites in two different work environments and to predict the attenuation of exposure-response relationships based on these measures. Methods: Parallel measurements of air and urine were performed among workers exposed to monoterpenes in sawmills (urinary metabolite: verbenol) and styrene in reinforced plastics factories (urinary metabolite: mandelic acid). Results: Among the sawmill workers, variance components of the air and urinary verbenol results were similar; for the reinforced plastics workers the estimated between-worker variance component was greater for styrene in air than mandelic acid in urine. This suggests that attenuation bias would be about equal if air or biological monitoring were employed for monoterpene exposures, but would be greater if urinary mandelic acid were used instead of airborne styrene in an investigation of styrene exposure. Conclusions: Personal air samplers provide data with similar or superior quality to urinary metabolites as measures of exposure to these monoterpenes in sawmills and styrene in reinforced plastics factories.